Design and implementation of incentive based smart plastic bottle disposal system - Rahman, Noshin Tarannum; Shaikat, Md Al Hasan; Jobayer, Md; Antor, Md Borhan Uddin (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2023.